Penerapan Scattergories Game in Teaching Untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris pada Siswa Kelas III MI Nurul Huda Banyubang - Siswandi; Aisyatum Bella; Aji Syahroni Muhsin; Nur Laili Dina Hafni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted with the aim of describing the level of learning achievement through the use of the Scattergories Game in Teaching the English vocabulary mastery of fifth-grade students at MI Nurul Huda Banyubang. The focus of the study was to improve the mastery of noun and verb vocabulary within the daily activities’ topic, particularly parts of the body, as well as to identify supporting factors in the implementation of Scattergories Game in Teaching. The study was carried out using a Classroom Action Research (CAR) design, with data collected through observation, interviews, and testing. The participants of this study consisted of 14 students. The findings revealed that the implementation of the Scattergories Game in Teaching students better understand, remember, and articulate vocabulary with greater ease. In addition, the use of Scattergories Game in Teaching encouraged active student participation in the learning process and built their confidence in using vocabulary in both oral and written contexts. Based on the findings from the initial test (Cycle I) and the final test (Cycle II), there was a noticeable improvement in the mastery of both noun and verb vocabulary after the application of the game-based learning method. From the data analysis, it can be concluded that Scattergories Game in Teaching is an effective, engaging, and enjoyable learning medium that supports the development of English vocabulary skills at the elementary school level.